98.5k views
5 votes
3(x - 2) = 5(x + 4)



2 Answers

3 votes

Answer:

The answer is
x = -13 .

Step-by-step explanation:

Solve the equation:


3(x -2) = 5(x + 4)

Use Distributive Property:


3(x -2) = 5(x + 4)


3x - 6 = 5x + 20

-Subtract
5x from
3x :


3x - 6 -5x = 5x -5x + 20


-2x - 6 = 20

-Add both sides by
6 :


-2x - 6 + 6 = 20+6


-2x = 26

-Divide both sides by
2 :


(-2x)/(-2) = (26)/(-2)


x = -13

So, now you have found the answer.

User Dmitry Dyachkov
by
5.5k points
3 votes

Answer:

Uh first of all this is algebra but I'll answer this

First distribute the three and 5 (Multiply them by both terms inside parenthesis.

3x-6=5x+20

Then add like terms

8x=14

Divide 8 by 8 and 8 by 14

x = 14/8

Step-by-step explanation:

User Tim Reistetter
by
4.9k points